Wound grading and surgical site infection following caesarean section - Arya, Kavita; Ram, Kishna; Hooja, Nupur; Singh, Neha; Jaiswal, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Surgical site infection (SSI) following caesarean section can adversely influence the postpartum period for the women. The objective of the study was to study the extent of infection and the microbiological flora in cases of surgical site infection following caesarean section. Methods: Women undergoing caesarean section amongst women admitted in labour ward were followed till discharge for any surgical site infection Detailed assessment of the wound was done. Any discharge if present was taken for culture. Results: 88.88% had normal wound healing, implying no infection. Of those with abnormal wound, 22% had serosanguinous or purulent discharge. Most had superficial incisional SSI. Enterococcus faecalis and Staphylococcus were the commonest organisms grown on culture. Conclusions: All surgical site infections should be looked into as early as possible and managed appropriately.